Teaching Portuguese and Deaf in São Tomé and Príncipe: from a paradigm of exclusion to inclusion - Lima, Hildomar José de (2019)
In Sao Tome and Principe and until 2013, Deaf children did not attend to school because, according to the teachers, they did not "learn anything". Isolated, without other peers to communicate, they felt unprotected and outcast in a society that did not welcome them. In 2013, due to the humanitarian missions of otolaryngology, this situation was detected and a project for educational inclusion was proposed. From a linguistic emergency project where the Sign Language of São Tomé and Príncipe was born, a "pilot group" was created, integrating 1st enrolled Deaf students in the regular school. In this process, a Portuguese handbook for the deaf was prepared. This handbook starts from the Sign Language of São Tomé and Príncipe to the comprehension and learning a second language from a different modality. In this descriptive article, we intend to interweave the two projects, showing and discussing the scientific and pedagogical options taken so that exclusion can be achieved.